An empirical model relating Supply Chain Sourcing performance, Making performance and Delivery performance to Company Performance - Mohanram, Satish; N, Vivek (Journal of Contemporary Research in Management (JCRM), 2014)
In today’s complex Business scenario, success to an organization is not easy. Every company works hard to better their products and make their supply chain more efficient and effective. R&D is about creativity and being innovative, to bring unique value propositions and solutions to the customers. There is very little that can be done to control it. Whereas, the area of Supply chain is one that can be tweaked to deliver performance, starting from providing the best in class service to customers to be able to push the profits up. This research paper is an initiative to establish a relationship between the components of Supply chain, namely Plan, Source, Make, Deliver and the overall Company Performance. A random set of 54 firms from Chennai have been studied with an objective to find a relationship between the components of Supply chain and the company performance. These firms were administered a structured questionnaire containing pre validated scales to measure the Supply chain components and relative performance of these organizations. After the data was collected, the scales were purified using Loading values and Composite reliability. The resultant purified scales were then tested for convergent validity using PLS path modeling software (Visual PLS). Once the constructs were both reliable and valid, the impact of supply chain components on company performance was tested using bootstrapping method. The result shows that there is a significant correlation between the Sourcing, Delivery functions of the Supply chain and the company performance. The making function does not seem to have a significant impact on the company performance.